Revisiting the formation of universal competencies of foreign students - Nikolay Grigorievich Spichak; Irina Valerievna Fedorova (Вестник Майкопского государственного технологического университета)
Foreign citizens study at Russian universities according to educational programs in accordance with the Federal State Educational Standard, designed for pre-university training of Russian citizens. This is especially evident in the formation of universal competencies (UC). The identification and search for the solution to the problems that arise in this case determine the relevance of the research. We set a goal to determine how significant the differences were between the content of pre-university Russian and foreign education, which is necessary for the formation of UC-11 – citizenship and UC-9 associated with it – inclusive culture, using the method of comparative analysis. Documents  on foreign education served as the material.When developing an educational program in terms of the formation of UC-11, universities take into account continuity with the general educational subject of social science, which Russian students study at a basic or advanced level. In this regard, the content of foreign education was assessed from the standpoint of the presence of the disciplines of the subject area «Social sciences». The analysis carried out showed their complete or partial absence in pre-university foreign education. Meanwhile, it turned out that the inclusive position of many foreign students, unlike Russian students, was practically formed. Thus, the university needs to develop individual educational programs for foreign students, providing for the expansion of the list of variable and optional disciplines, changing the ratio of contact work with a teacher and student’s independent work. The optimal form remains the previous or parallel development of a specially designed additional educational program.